MENGATASI OVERLOAD MENGGUNAKAN LINUX VIRTUAL SERVER SEBAGAI LOAD BALANCING PADA SERVER E-LEARNING UNIVERSITAS BINA DARMA - Suryayusra, Suryayusra (JURNAL ILMIAH MATRIK, 2012)
Provision of information services on a system relies heavily on existing infrastructure. At Bina Darma University server has the functions of the application and hold a very important role in carrying out teaching and learning activities. One function of these servers are running the e-learning applications to support teaching and learning or supplements that are given regardless of the regular meeting (in class). In daily operations, (MIS-CUTS Bina Darma) states that e-learning server must serve 4437 users with a variety of activities. Many activities that must be completed within a time resulted in Apache connection flooded with requests that exceed the ability of so many processes that are not resolved. LVS can be applied to generate a load balancing. By providing a computer unit that acts as a director and two or more computers that will do the (real server) will improve performance so that availability can be generated by the method of load balancing. Keywords: Load Balancing, Linux Virtual Server, Network Address Translation, E-learning